2011
DOI: 10.1371/journal.pone.0018876
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity fMRI of the Rodent Brain: Comparison of Functional Connectivity Networks in Rat and Mouse

Abstract: At present, resting state functional MRI (rsfMRI) is increasingly used in human neuropathological research. The present study aims at implementing rsfMRI in mice, a species that holds the widest variety of neurological disease models. Moreover, by acquiring rsfMRI data with a comparable protocol for anesthesia, scanning and analysis, in both rats and mice we were able to compare findings obtained in both species. The outcome of rsfMRI is different for rats and mice and depends strongly on the applied number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
226
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(250 citation statements)
references
References 46 publications
23
226
1
Order By: Relevance
“…Furthermore, we successfully applied a modelfree probabilistic independent component analysis strategy to identify a group-based functional bilateral sensorimotor cortical network in rat brain, in addition to other networks such as a bilateral cingulate-thalamic network. Despite differences in rat strain, anesthesia, ICA algorithm, and number of components, our findings are largely in agreement with previous studies that also demonstrated predominantly bilateral functional networks in rat brain (Hutchison et al, 2010;Jonckers et al, 2011). Subsequent analyses demonstrated that both interhemispheric functional connectivity and ipsilesional intrahemispheric signal coherence in sensorimotor cortex and cingulate-thalamic network were significantly reduced after medium and large stroke, particularly at subacute stages.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we successfully applied a modelfree probabilistic independent component analysis strategy to identify a group-based functional bilateral sensorimotor cortical network in rat brain, in addition to other networks such as a bilateral cingulate-thalamic network. Despite differences in rat strain, anesthesia, ICA algorithm, and number of components, our findings are largely in agreement with previous studies that also demonstrated predominantly bilateral functional networks in rat brain (Hutchison et al, 2010;Jonckers et al, 2011). Subsequent analyses demonstrated that both interhemispheric functional connectivity and ipsilesional intrahemispheric signal coherence in sensorimotor cortex and cingulate-thalamic network were significantly reduced after medium and large stroke, particularly at subacute stages.…”
Section: Discussionsupporting
confidence: 92%
“…fmrib.ox.ac.uk/fsl), to extract a group-averaged functional network that included the bilateral sensorimotor cortex. This data-driven approach allows unbiased identification of whole functional networks from included animals, without the need to coregister to an extrinsic rat brain atlas to select diverse brain regions that are assumed to be part of a larger functional network (Hutchison et al, 2010;Jonckers et al, 2011). We found that analysis with seven components yielded a component of which the anatomical pattern most ideally matched with the bilateral sensorimotor cortices (see Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Using this technique, functional connectivity (FC) is defined as the temporal correlation of these fluctuations between different brain regions [26]. Coherence of low frequency fluctuations of the BOLD signal has been shown in different mammalian species including mice [27], rats [28], monkeys [29], and humans [26]. This paper shows the first application of rsfMRI in a non-mammalian species, a pigeon.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are similarities, many discordant results are observed between studies. One reason for this may be that different labs adopted different anaesthetic regimens (Jonckers et al, 2011;Grandjean et al, 2014b;Mechling et al, 2014;Sforazzini et al, 2014;Liska et al, 2015;Zerbi et al, 2015).…”
Section: MVmentioning
confidence: 99%
“…Its inventor shared the Nobel Prize in Physiology or Medicine in 2003 (Huettel et al, 2009). Discovered in rats (Ogawa et al, 1990), the application areas of BOLD fMRI have been expanded not only to humans (Kwong et al, 1992), but also monkeys (Vincent et al, 2007) and now mice (Jonckers et al, 2011). Its contributions to both clinical and scientific research are still growing steadily.…”
Section: Blood-oxygen-level-dependent (Bold) Functional Mrimentioning
confidence: 99%